Mackenzie and his Voyageurs: By Canoe to the Arctic and the Pacific, 1789-93: - Woollacott, Arthur P. (Author) (J.M. Dent and Sons, ltd., 1927)
by Arthur P. Woollacott. In the preparation of this essay, Mackenzie's narrative, as contained in the original edition of his Voyages, 1801, was used as a basis.--p. v.